Appeals mechanism in international investment disputes (New York, 2008)
"This volume brings together significant contributions from leading voices in academia, the legal profession and government on the increasingly important topic of international investment and the legal system in which it operates. With the burgeoning size of international capital flows matched only by an explosion in international agreements intending to regulate the field, there is increasing potential for incoherence amongst and between treaties and arbitral decisions. The Columbia Program on International Investment, a joint undertaking of Columbia Law School and the Earth Institute, has taken on the challenge of the international investment law system and in April 2006 held its first symposium, "Coherence and Consistency in International Investment Law." Appeals Mechanism in International Investment Disputes is one important result: It compiles, compares and contrasts the analysis and arguments of the leading scholars, practitioners and government officials on the future of the international investment law regime. Its special emphasis is on the question of an appellate body for international investment disputes. The authors also seek ways to streamline and improve the system, channeling the benefits of free trade and investment flows to people in both the developing and emerging markets. The Appendices provide readers with extensive background material to place the chapters into context. Selected sections include concise commentaries to further illuminate the timely themes covered by the chapters. The volume is singular in its success at bringing together so many exceptional individuals on a question of growing import-how to improve the international law regime to increase prosperity and further global development. If a reader wants to know what the influential voices in international law are saying right now, and in a concise and readable format, this is the publication to have."